Aquirufa antheringensis gen. nov., sp. nov. and Aquirufa nivalisilvae sp. nov., representing a new genus of widespread freshwater bacteria. Issue 9 (1st April 2019) - Pitt, Alexandra; Schmidt, Johanna; Koll, Ulrike; Hahn, Martin W.
Abstract : Three bacterial strains, 30S-ANTBAC, 103A-SOEBACH and 59G- WUEMPEL, were isolated from two small freshwater creeks and an intermittent pond near Salzburg, Austria. Phylogenetic reconstructions with 16S rRNA gene sequences and, genome based, with amino acid sequences obtained from 119 single copy genes showed that the three strains represent a new genus of the family Cytophagaceae within a clade formed by the genera Pseudarcicella, Arcicella and Flectobacillus . blast searches suggested that the new genus comprises widespread freshwater bacteria. Phenotypic, chemotaxonomic and genomic traits were investigated. Cells were rod shaped and were able to glide on soft agar. All strains grew chemoorganotrophically and aerobically, were able to assimilate pectin and showed an intense red pigmentation putatively due to various carotenoids. Two strains possessed genes putatively encoding proteorhodopsin and retinal biosynthesis. Genome sequencing revealed genome sizes between 2.5 and 3.1 Mbp and G+C contents between 38.0 and 42.7 mol%. For the new genus we propose the name Aquirufa gen. nov. Pairwise-determined whole-genome average nucleotide identity values suggested that the three strains represent two new species within the new genus for which we propose the names Aquirufa antheringensis sp. nov. for strain 30S-ANTBAC T (=JCM 32977 T =LMG 31079 T =DSM 108553 T ) as type species of the genus, to which also belongs strain 103A-SOEBACH (=DSM 108555=LMG 31082) and Aquirufa nivalisilvae sp. nov. for strain 59G-WUEMPEL T (=LMG 31081 T =DSM 108554 T ).